A description of a hepatitis A outbreak in men who have sex with men and public health measures implemented in Seine-Maritime department, Normandy, France, 2017 - Nathalie Nicolay; Maggie Le Bourhis-Zaimi; Anais Lesourd; Mélanie Martel; Anne-Marie; Stéphane Erouart; Manuel Etienne; Ndeindo Ndeikoundam Ngangro (BMC, 2020)
Abstract Background In 2016-2017, a European-wide circulation of genotype IA hepatitis A virus was responsible for hepatitis A outbreaks in men who have sex with men (MSM). This study aimed to describe the outbreak investigation in Seine-Maritime department (France) and the control measures implemented accordingly. Methods Outbreak description used data from mandatory reporting and enhanced surveillance of male cases. Confirmed case was genotype IA isolated, possible cases had no reported genotype information. Targeted control measures included communication on sexual practices at risk of hepatitis A transmission and two vaccination campaigns in April 2017 and January 2018. Characteristics of cases and vaccinees were described. We reported the best communication channel for relaying outbreak information and control measures based on the monitoring of social network activities and feedback from vaccinees. Results During the outbreak period (December 2016 to December 2017), a total of 48 confirmed outbreak cases and 30 possible outbreak cases were notified. Among them, 69 were male (88%). Two epidemic waves were observed. Cases encountered their partners through gay-dating apps (54%) and in one specific sauna (62%). In response to the outbreak, two vaccination campaigns were deployed. A total of 156 MSM were vaccinated, of whom 56 in a truck parked beside the sauna. Most of the vaccinees had been informed about the campaign through dating apps (44%). Community-based organizations involved in sexual health promotion and other gay social media were very proactive in sharing information about the outbreak and promoting the vaccination campaign through their social media account and also on site (gay venues). Vaccinees reported the same sexual practices at risk of hepatitis A transmission as cases. Conclusions In response to this massive hepatitis A outbreak that affected mostly MSM in Seine-Maritime department, vaccination campaign remained the cornerstone of prevention. Prevention officers from the community-based organization played a key role in vaccination promotion. Gay-dating apps and outdoor sessions of vaccination allowed to effectively reach MSM. Cost-effectiveness studies might analyze the interest of a continuous sexual health promotion including vaccination against hepatitis A in MSM through dating apps and social networks.